2012
DOI: 10.1186/cc11668
|View full text |Cite|
|
Sign up to set email alerts
|

n-3 fatty acid-enriched parenteral nutrition regimens in elective surgical and ICU patients: a meta-analysis

Abstract: IntroductionPrevious studies and a meta-analysis in surgical patients indicate that supplementing parenteral nutrition regimens with n-3 polyunsaturated fatty acids (PUFAs), in particular eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), is associated with improved laboratory and clinical outcomes in the setting of hyper-inflammatory conditions. Refined or synthetic fish oils are commonly used as a source of EPA and DHA. The objective of the present meta-analysis was to evaluate n-3 PUFA-enriched par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
154
1
18

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 149 publications
(179 citation statements)
references
References 29 publications
6
154
1
18
Order By: Relevance
“…These data from a recent systematic analysis in 23 RCTs, including 1502 surgical and intensive care unit (ICU) patients, demonstrated that fish oil containing lipids reduced LOS and infectious complications versus traditional soy-only lipids. 99 …”
Section: Postoperative Nutritionmentioning
confidence: 99%
“…These data from a recent systematic analysis in 23 RCTs, including 1502 surgical and intensive care unit (ICU) patients, demonstrated that fish oil containing lipids reduced LOS and infectious complications versus traditional soy-only lipids. 99 …”
Section: Postoperative Nutritionmentioning
confidence: 99%
“…The least antibiotic demand was seen in patients receiving 0.15-0.2 g/kg/day of the fish oil. Pradelli et al 54 performed a metaanalysis of controlled trials of surgical and intensive care unit (ICU) patients receiving parenteral nutrition who were randomized to receive omega-3 PUFA-enriched lipid emulsions or not. A total of 23 studies involving 1,502 patients were analyzed.…”
Section: Omega-3 Fatty Acids and Infectionmentioning
confidence: 99%
“…En un metaanálisis de Pradelli y cols. (25) concluyeron que, en pacientes críticos y quirúrgicos, la administración de EL con AP se asocia con una reducción significativa de infecciones y de días de estancia hospitalaria. En otro metaanálisis en paciente crítico, Palmer y cols.…”
Section: Discussionunclassified